Effects of Biochemical, Antimicrobial, Green Synthesis Characterizations on Aqueous Extract of Murraya koenigii Leaf and its Influence on Hypertension using Molecular Docking Approach - Oseni, Margaret Oladunni; Oladipupo, Beauty; Adewumi, Funmilayo; Mpetcha, Andrie; Oseni, Olatunde Abass (International Journal of Innovative Research in Medical Science, 2025)
Background & Objective: Plants have been tremendously utilized as a source of medicine, therefore this study aimed at investigating the biochemical composition, antimicrobial properties and green synthesis characterization of Murraya koenigi (Curry leaf) using its aqueous extract. Method: Standard methods were used to analyse the various parameters of nutritional, antinutrients, phytochemicals, antioxidants, antimicrobial green synthesis and molecular docking. Results & Conclusion: The results of proximate composition revealed a nutrient-dense profile, it also contained nutritionally valuable minerals while anti-nutrient assessment showed minimal content within the daily recommended allowance. The phytochemical screening of the aqueous and ethanol extracts showed the presence of some bioactive compounds like flavonoids, alkaloids, tannins, and phenol. The antioxidant evaluation demonstrated remarkable free radical scavenging abilities, high content of some antioxidant compounds. Antimicrobial evaluation of the aqueous extract and its synthesized nanoparticles of silver (AgNP), copper (CuNP) and zinc (ZnNP) against a range of bacterial and fungal pathogens showed remarkable inhibitory zones. FTIR analysis of the aqueous extract also revealed the presence of some functional groups such as phenolics, carboxylic acids, and amines while UV/Visible spectrophotometric scanning displayed intensive absorption of light by the inherent chemical substances of the aqueous and synthesised nanoparticle solutions. Bioinformatics approaches identified potential molecular targets for the bioactive compounds. Docking simulations revealed strong binding affinities between key phytochemicals, such as citral, β-myrcene, and geraniol, and the 1Y9R (PDB ID MCR) receptor, demonstrating their potentials as therapeutic agents. Molecular interaction studies further illustrated the compatibility of these compounds with active site residues, reinforcing their drug-likeness properties. Clustering analysis of the major phytochemicals provided insights into their synergistic bioactivity, enhancing the overall therapeutic potentials of the extract.